Risk of impaired school performance in children hospitalized with concussion: a population-based matched cohort study - Reidar P Lystad; Anne McMaugh; Geoffrey Herkes; Gary Browne; Tim Badgery-Parker; Cate M Cameron; Rebecca J Mitchell (Concussion)
Aim: To examine the impact of concussion on objective measures of school performance. Materials & methods: Population-based matched cohort study using linked health and education records of young p...